Growth Performance, Haematological Parameters, Intestinal Microbiology, and Carcass Characteristics of Broiler Chickens Fed Two-Stage Fermented Cassava Pulp during Finishing Phase - S. Sugiharto; T. Yudiarti; I. Isroli (Faculty of Animal Science, Bogor Agricultural University, 2019)
This study aimed to investigate the effect of two-stage fermented cassava pulp (FCP) on growth, blood parameters, intestinal microbiology and carcass characteristics of broilers. Two hundreds Lohmann broiler chicks were used from days 22 to 38 and allotted to CONT (maize-soybean-meal-based finisher diet), FCP-10 (finisher diet containing 10% FCP), FCP-15 (15% FCP) and FCP-20 (20% FCP). FCP was included into finisher diet at the expense of maize. On day 38, one bird per replicate was blood sampled and slaughtered. Ileal and caecal digesta and duodenal, jejunal and ileal segments were obtained for intestinal microbiology and villi height measurements. Breast muscle was obtained for meat colour determination. FCP-10 had a higher (p≤0.05) body weight gain than CONT. Feed intake was highest (p≤0.05) in FCP-15 and the lowest (p≤0.05) in CONT. Feed conversion ratio was lowest and highest in FCP-10 and FCP-15, respectively (p≤0.05). FCP-20 had a lower (p≤0.05) abdominal fat than CONT and FCP-10. CONT had lower (p≤0.05) serum total triglycerides than FCP-15 and FCP-20. Duodenal villi height for FCP-20 was higher (p≤0.05) than that for CONT and FCP-15. The ileal villi height for FCP-20 was lower (p≤0.05) than that for CONT and FCP-15. The wings relative weight was higher (p≤0.05) in FCP-20 than in FCP-10 and FCP-15. FCP-15 and FCP-20 had higher (p≤0.05) L* (lightness) values than CONT. In conclusion, feeding two-stage FCP up to 20% had no deleterious effect on growth, haematological parameters, intestinal microbiology and carcass characteristics. Feeding two-stage FCP at a level of 20% reduced the abdominal fat content and increased duodenal villi height of broilers.